PENERAPAN BUDIDAYA PADI DENGAN METODE SRI (SISTEM OF RICE INTENSIFICATION) DI DESA PATEMON KECAMATAN BOJONGSARI KABUPATEN PURBALINGGA - Okti Herliana; Sapto Nugroho Hadi; Wilis Cahyani (Universitas Jenderal Soedirman, 2019)
Patemon Village is located in the District of Bojongsari, Purbalingga Regency, approximately 17 Km from the General Soedirman University Campus with a total of 528 Family Heads and a population of 4350 people. The livelihoods of the population are mostly farmers. Agricultural potential of Patemon Village, Bojongsari Subdistrict includes: rice, corn, soybeans and cassava. The area of paddy fields in this village reaches 128,000 ha but unfortunately its productivity is still relatively low. This is because farmers are still implementing conventional cultivation systems and lack of knowledge about integrated crop management. This activity aims to provide knowledge and examples of alternative rice cultivation methods, namely rice farming using the SRI (System of Rice Intensification) method with the application of straw compost and vegetable pesticides. This activity involved the target audience, namely the